Залюднення Дніпро-Донського Лісостепу у VI ст. до н. е.: демографічний вибух чи нова міграція? - Гречко, Д.С. (Археологія і давня історія України, 2022)
Стаття присвячена одній з важливих сторінок етнокультурної історії населення Дніпровського лісостепового Лівобережжя протягом скіфського часу — залюдненню лісостепових частин річок Сули, Псла, Сейму, Сіверського Дінця та Середнього Дону. Наведено аргументи про зв’язок цієї міграції з подіями перехідного періоду, а її вихідну територію запропоновано вважати Дністро-Дніпровський Лісостеп. The paper is devoted to one of the important pages of the ethnic and cultural history of the population of the forest-steppe of Dnieper Left Bank area in the Scythian Age — settling of the forest-steppe parts of the basins of Sula, Psel, Seim, Seversky Donets and Middle Don rivers. The analysis of material culture of new sites in the region allowed us to make several conclusions. Most of the handmade pottery forms and the main decorative elements of the ceramic complex of the sites of Eastern Bil’s’k type dating to the middle — second half of the 6th century BC are genetically related to the forest- steppe of Dnieper Right Bank area and to more western regions of forest-steppe. Materials from the Vorskla sites of the second half of 6th century BC are significantly differ and continue the local traditions of the previous time. The differences are clearly visible when comparing the material culture of that time of Western and Eastern fortifications of the Bil’s’k settlement. This indicates that the settlements of the Dnieper-Donets forest-steppe at this time did not reason due to the demographic explosion in the Vorskla and Psel interfluves. The set of the jewelry and a costume of the migrants of the mid-6th century BC at the forest-steppe of Dnieper Left Bank area has straight analogies among the materials of the Right Bank of the Early Scythian Age. It can be assumed that the initial migration areas could have been the Kyiv Dnieper region, the eastern and western Podolyan groups of the sites where the settlement systems and burials disappeared simultaneously. The participation of the population from Ros’ river and other regions in this process can’t be ruled out. Thus, in the development of the settlement system of the forest-steppe of Dnieper Left Bank area two main events that radically influenced the settling of the region by the sedentary population during the Scythian Age can be distinguished. First, during the Zhabotin period, on the territory of the Lower Vorskla and the Vorskla and Psel interfluve the settlements of the migrants from the forest-steppe of Dnieper Right Bank area appeared. In the Middle Scythian Age, as a result of the new movement of the tribes from the west, a ramified settlement system emerged. New migrants have created the settlements that are geographically united into several local groups: two in Sula, Vorskla and Seim basins, three in Psel and one each in Uday, Merle and Kolomak basins. It is interesting that new groups of the population bypassed in their resettlement the territories occupied at that time by migrants of the Zhabotin period.